Spin dynamics in cuprate perovskites: Spin Models - Sherman, A.; Schreiber, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Results obtained with the use of the t–J model of Cu–O planes and Mori’s projection operatorformalism are compared with data of neutron scattering experiments in lanthanum and yttrium cuprates. This comparison allows us to interpret the intensive peak at the antiferromagnetic wave vector observed in yttrium cuprates as a manifestation of excitations of localized Cu spins. The high-frequency incommensurability detected both in lanthanum and yttrium cuprates is connectedwith the dispersion of these excitations, while the low-frequency incommensurability arises due toa dip in the spin-excitation damping at the antiferromagnetic wave vector. For moderate doping the dip stems from the weakness of the interaction between the spin excitations and holes near hot spots. It is conjectured that the dissimilarity of the susceptibility frequency dependencies in yttrium and lanthanum cuprates may be connected with different values of the hole bandwidth and damping in these crystals.